Diagnostic performance of fusion of myocardial perfusion imaging (MPI) and computed tomography coronary angiography - Santana, Cesar A.; Garcia, Ernest V.; Faber, Tracy L.; Sirineni, Gopi K. R.; Esteves, Fabio P.; Sanyal, Rupan; Halkar, Raghuveer; Ornelas, Mario; Verdes, Liudmila; Lerakis, Stamatios; Ramos, Julie J.; Aguadé-Bruix, Santiago; et al. (Journal of nuclear cardiology, 2009)
Background We evaluated the incremental diagnostic value of fusion images of coronary computed tomography angiography (CTA) and myocardial perfusion imaging (MPI) over MPI alone or MPI and CTA side-by-side to identify obstructive coronary artery disease (CAD > 50% stenosis) using invasive coronary angiography (ICA) as the gold standard. Methods 50 subjects (36 men; 56 ± 11 years old) underwent rest-stress MPI and CTA within 12-26 days of each other. CTAs were performed with multi-detector CT-scanners (31 on 64-slice; and 19 on 16-slice). 37 patients underwent ICA while 13 subjects did not because of low (<5%) pre-test likelihood (LLK) of disease. Three blinded readers scored the images in sequential sessions using (1) MPI alone (2) MPI and CTA side-by-side, (3) fused CTA/MPI images. Results One or more critical stenoses during ICA were found in 28 patients and non-critical stenoses were found in 9 patients. MPI, side-by-side MPI-CTA, and fused CTA/MPI showed the same normalcy rate (NR:13/13) in LLK subjects. The fusion technique performed better than MPI and MPI and CTA side-by-side for the presence of CAD in any vessel (overall area under the curve (AUC) for fused images: 0.89; P = .005 vs MPI, P = .04 vs side-by-side MPI-CTA) and for localization of CAD to the left anterior descending coronary artery (AUC: 0.82, P < .001 vs MPI; P = .007 vs side-by-side MPI-CTA). There was a non-significant trend for better detection of multi-vessel disease with fusion. Conclusions Using ICA as the gold standard, fusion imaging provided incremental diagnostic information compared to MPI alone or side-by-side MPI-CTA for the diagnosis of obstructive CAD and for localization of CAD to the left anterior descending coronary artery.